Prediksi Harga Saham Bank BCA Menggunakan Prophet - Beno Jange (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to test the Prediction of Bank BCA Stock Price using the Prophet. Prophet is a model for generating forecasts based on historical data. The data in this study is the stock price data of Bank BCA for 4 (four) years, namely from 01-01-2017 to 31-12-2020. The results of this study indicate a fairly good prediction accuracy with a MAPE of 5.37 percent with hyper parameter tunings; predictions are a little less good for several months in 2020 due to the effects of holidays caused by the Covid-19 pandemic and large-scale social restrictions (PSBB)